III. DECREASE OF LABELED DNA IN CELLS OF THE ADRENAL MEDULLA AFTER INTERMITTENT EXPOSURE TO COLD - Pelc, S. R. (The Rockefeller University Press, 1969)
Italico rats were injected with thymidine-(3)H 6 hr after the end of 300 hr of intermittent cold treatment. This plan of experiment ensured replacement in the adrenal medulla of lost DNA which is specifically sensitive to cold treatment and has a labeling index sufficiently high for statistical evaluation. The labeling index in the adrenal medulla decreases to one-half of the initial value within 10 days in animals subjected to further intermittent cold treatment and within 32 days in animals kept at room temperature. The very low mitotic index and the absence of doubling of the labeling index show that the observed labeling cannot be ascribed to pre-mitotic DNA synthesis. The concept of metabolic DNA adequately explains the findings.